Evaluation of skill-based training program on Integrated Management of Neonatal and Childhood Illnesses (IMNCI) - Dhikale, Prasad Tukaram; Kembhavi, Ravindra Shivappa; Chavhan, Smita Santosh; Miranda, Roshni Cynthia; Supe, Kirti Amit; Ingale, Aniket Ravindra (Indian Journal of Community Health, 2024)
Objectives: To assess student reactions to the skill-based training program on IMNCI. To assess student learning in the skill-based training program on IMNCI by OSCE and retro-pre feedback. To assess the reaction of students to OSCE as an assessment tool. Material and Methods: It was a mixed method interventional educational research. Students were assessed by using OSCE stations, retro pre feedback, and open ended questions about the training program and OSCE. Results: Retro?pre feedback of self?assessment of the 75 students shows that, after the training program, there is a significant increase in the self perceived post-test scores of Knowledge of Importance of IMNCI (2–4), Chart booklet (1.5–3.9), Skills of assessing the child for danger signs (1.7–3.9), cough (1.9–3.9), diarrhoea (2.1–4.2), anemia (2.2 –4.1), malnutrition (2.2 –4.2), counseling the care giver of the child (2-4.2). The students liked the skills taught interactively through videos, case scenarios, and role plays. Student liked the OSCE because of the clinical scenarios, photos, diverse cases were evaluated. Conclusions: Overall, the training program was taken well by the students and their IMNCI skills were improved.